Novel treatment possibilities of invasive aspergillosis - G. A. Klyasova (Онкогематология)
Invasive aspergillosis is the leading fungal infection in patients with hematological malignancies. The review represents the incidence of invasive aspergillosis in different groups of patients, risk factors for its development, treatment options, including the new drug isavuconazole.